2022
DOI: 10.1088/1361-6528/aca1c9
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic modeling of interfacial abruptness in axial nanowire heterostructures

Abstract: Kinetic modeling of the formation of axial heterostructures in III-V nanowires grown by the Au-catalyzed vapor-liquid-solid method is presented. We link the mass balance in the droplet to the crystallization rates of different III-V pairs at the liquid-solid interface. This allows us to describe how the chemical composition changes across a nanowire heterostructure and study the influence of the growth parameters on the interfacial abruptness. It is shown that, at high enough supersaturation in liquid, there i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 35 publications
(67 reference statements)
0
8
0
Order By: Relevance
“…The group-V concentration in the droplet is in the order of 0.01 or even less, which is much lower than the total group-III concentration according to the data of Refs. [ 20 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. This fundamental property holds regardless of the fact that the droplets catalyzing the VLS growth of InGaAs [ 15 , 29 , 31 , 32 ], InGaP [ 17 ], or InGaN [ 24 ] NWs are In-rich, while the droplets catalyzing the VLS growth of AlGaAs NWs are Ga-rich [ 20 , 29 , 31 ].…”
Section: Limiting Steps Of Group-iii and Group-v Element Incorporationmentioning
confidence: 99%
See 3 more Smart Citations
“…The group-V concentration in the droplet is in the order of 0.01 or even less, which is much lower than the total group-III concentration according to the data of Refs. [ 20 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. This fundamental property holds regardless of the fact that the droplets catalyzing the VLS growth of InGaAs [ 15 , 29 , 31 , 32 ], InGaP [ 17 ], or InGaN [ 24 ] NWs are In-rich, while the droplets catalyzing the VLS growth of AlGaAs NWs are Ga-rich [ 20 , 29 , 31 ].…”
Section: Limiting Steps Of Group-iii and Group-v Element Incorporationmentioning
confidence: 99%
“…Here, and are the chemical potentials of A and B atoms in liquid in thermal units, which contain the chemical potentials of pure liquids and , logarithmic terms in concentrations and interaction terms and . These interaction terms generally depend on the atomic concentrations , , and (with the Au concentration given by ) [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. The number of variables is reduced from three to two for self-catalyzed VLS NWs with .…”
Section: Liquid–solid Distributionmentioning
confidence: 99%
See 2 more Smart Citations
“…To this end, the seminal work of Biefeld [ 129 ] remains the only approach to access the behavior of vapor–solid distributions under a varying V/III flux ratio, but this model is restricted to the reaction-limited growth kinetics of epilayers and is not adopted for nanowires. Time-dependent generalizations of compositional models, which are used to model the interfacial abruptness in III–V nanowire heterostructures [ 21 , 111 , 115 , 116 , 127 , 148 ], were beyond the scope of this work (a review can be found, for example, in Ref. [ 142 ]).…”
Section: Discussionmentioning
confidence: 99%